Biodiesel from microalgae: Recent progress and key challenges. (November 2022) - Kim, Jee Young; Jung, Jong-Min; Jung, Sungyup; Park, Young-Kwon; Tsang, Yiu Fai; Lin, Kun-Yi Andrew; Choi, Yoon-E; Kwon, Eilhann E.
Abstract: High lipid content and excellent CO2 fixation capability of microalgae by photosynthesis have made microalgal biodiesel (BD) a promising carbon-neutral fuel. Nonetheless, the commercialization of BD has not yet been realized because of expensive and energy-intensive cultivation, pretreatment, and BD conversion processes in reference to 1 st generation BD production. To resolve the issues, this study comprehensively reviewed the current technical developments of microalgal BD production process and suggested promising future studies. Current microalgal BD production processes highly rely on the processes developed from 1 st generation BD process, namely base-catalyzed transesterifications. However, the base-catalyzed suffers from saponification reaction and low production yield due to high water and free fatty acid contents in microalgae. Vigorous pretreatments such as dewatering, drying, esterification of free fatty acid, and purification are required for high yield of microalgal BD production, making this process economically not attractive. As efforts to construct new transesterification platform, novel approaches tolerant to impurities such as thermally induced non-catalytic transesterifications were suggested. The thermally induced reactions allowed in situ conversion of microalgal lipid into BD (≥ 95 wt.% yield) within 1 min of reaction at ≥ 350 ˚C. This process resists to presence of water and free fatty acids and does not require lipid extraction process. To make this process more promising, it was suggested lowering reaction temperature for thermally induced transesterifications. In addition, pilot study, in-depth life cycle assessment, and economic analysis were suggested to assess economic viability and environmental impacts.